Randolph Bourne and the Politics of Cultural Radicalism - Vaughan, Lesie J. (University Press of Kansas, 1997)
In the "little rebellion" that swept New York's Greenwich Village before World War I, few figures stood out more than Randolph Bourne. Hunchbacked and caped-the "little sparrowlike man" of Dos Passos' U.S.A.-Bourne was an essayist and critic most remembered today for his opposition to U.S. military involvement in Europe and his assertion that "war is the health of the state." A frequent contributor to The New Republic, he died in 1918 at the age of 32, arguing that a "militaryindustrial" complex would continue to shape the policies of the modern liberal state.Bourne is also recognized as one of the founders of American cultural radicalism, revered in turn by Marxists, antifascists, and the New Left. Through his writings, he debated issues that were cultural as well as political from a position he described as "below the battle," rejecting the either/or political options of his day in favor of a viewpoint that argued outside the terms set by the establishment.In her new study of Bourne's political thought, Leslie Vaughan maintains that this position was not, as others have contended, a retreat from politics but rather a different form of political engagement, freed from the suppositions that impede genuine debate and democratic change. Her analysis challenges previous readings of Bourne's politics, showing that he offered nonstatist, neighborhoodbased politics in America's modern cities as a practical alternative to involvement in the national state and its militarism. By demonstrating Bourne's emphasis on politics as local, multiethnic, and intergenerational, Vaughan shows that his thought offered a new political discourse and set of cultural possibilities for American society in an era he was the first to label as "postmodern." Returning to the influence of Nietzsche on his thought, she also explores the role Bourne played in the creation of his own myth.Eighty years later, Bourne can be seen to stand at the cusp of the modern and the postmodern worlds, as he speaks to today's multiculturalist movement. In reexamining Bourne's writings, Vaughan has located the roots of twenthiethcentury radical thought while repositioning Bourne at the center of debates about the nature and limits of American liberalism.